PERLINDUNGAN HUKUM BAGI KONSUMEN PENGGUNA TENAGA LISTRIK DALAM USAHA HOME INDUSTRI AKIBAT TIDAK STABILNYA ALIRAN LISTRIK PADA PLN SAMARINDA - Mahfud Mahfud (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT        User complaints forms Power / consumers in terms of the occurrence or non kelalain and PT PLN (Persero) APJ Samarinda, namely: Fluctuations or increases in voltage (voltage) is quite high. The increase in voltage occurs suddenly and resulted in dozens of electronic appliances such as refrigerators, televisions, VCD player was broken and there were to catch fire; Electricity died suddenly and without peinberitauan advance; The increase in electricity tariff (TDL) every quarter. If it is associated with the right of consumers to obtain electricity at a reasonable price of article 34, paragraph 1 (c), the TDL a quarterly basis is not feasible, given the income levels do not go up every three months. In one year alone, revenue is not necessarily rise; Counting electricity bills are not in accordance with the usage. This can happen because of recording errors bill, the account used to swell due to the previous billing system "shoot". The cost of electricity tariff increase of more than 30% (thirty percent), the imposition of business rates for household customers, and so on; Not to mention the length of realization of the demand decline for example, from 1,300 to 900 Kwh Kwh of power or 900 kWh to 450 kWh. Of course Sangai violate consumer rights, namely the right to choose the goods or services; Power outages done unilaterally. In this case the customer is supposed to get the return Deposit subscriptions in accordance with Article 7, paragraph (5) SPJBTL.        To be able to claim their right to compensation, consumers either alone or jointly, or through their proxies, can make efforts to settle the lawsuit for compensation by way: Come, deliberate and resolve themselves directly with the PT PLN; Complaints through YLKI; Seeked litigation through the District Court, where a lawsuit can be filed on the basis of breach of contract or tort. Obstacles that arise in the business settlement of a lawsuit against PT PLN (Persero), among others: The existence of Minimum Service Standards (SPM) which is owned by PT PLN (partners) APJ Samarinda, making these enterprises is difficult to be sued in the occurrence of a power outage for about of 3x24 consecutive hours; Consumers passive and uncooperative during the lawsuit settlement with PT PLN in mediation. This resulted in the settlement process stalled for granted without any settlement; Consumers "do not dare" manju to resolve the complaint through the courts. Lack of consumer knowledge about their rights and obligations as well as the efforts of what they can do when suffering losses due to violations committed by PT PLN.